The kingdom in the cradle - Atkins, James (Publishing House of the M.E. Church, South, 1905)
By way of suggestion -- A view of the kingdom -- The outgrowing power of Christianity -- Christ's doctrine of the child and the kingdom -- The child as the subject of religious education -- The educational function recognized -- The education of what? -- The church and the home -- The child in the home -- The place and status of the Sunday school -- Some essentials of successful Sunday-school work -- The Sunday school as a field of training -- Religion in popular education -- The church through all.